Effects of urbanization on multiple human perceived temperatures in South China - Lin, Lijie; Guo, Meiyu (Frontiers in Environmental Science, 2023)
Under the combined effects of global warming and local human activities such as urbanization, increasing populations are exposed to the threat of extreme heat events. While the effects of regional urbanization on the changes in air temperature and its extremes have been well studied, the effects on mean and extreme human perceived temperatures (HPT) are still to be explored. Based on a dynamic meteorological station classification approach, this study quantitatively assessed the impacts and relative contribution of urbanization on the mean and extreme HPT in South China by analyzing ten different HPT indicators and taking Guangdong Province as an example. It was found that for all HPT indicators, the mean HPT and the frequency of extreme HPT events in South China notably increased from 1971 to 2020, especially in the regions with comparatively higher levels of local urbanization (e.g., the Pearl River Delta). Urbanization contributed significantly to the long-term changes in both mean and extreme HPT in Guangdong. On average, the relative contributions of urbanization to the total increases in mean HPT and the frequency of extreme HPT events were 15.5% and 15.1%, respectively. These contributions vary across different HPT indicators, and the urbanization contributions to the HPT indicators that consider the combined effects of wind speed were even higher than those merely related to near-surface air temperature and humidity. Among different seasons, the contributions of urbanization to mean and extreme HPT in both fall and winter were greater than that in spring and summer. The findings reported here provide scientific advice for governments’ policy-making and adaption for human-perceived thermal comfort in subtropical humid climate zones.